2015
DOI: 10.1016/j.apm.2014.10.049
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Boltzmann simulation for mixed convection of nanofluids in a square enclosure

Abstract: In this paper, the lattice Boltzmann method is applied to investigate the natural and mixed convection of Al 2 O 3 /water nanofluids in a square enclosure. The Rayleigh number is considered from 10 3 to 10 6 to present the buoyancy effects. In mixed convection problems, the Richardson number representing the importance of natural convection relative to the forced convection is set to Ri=1, 5, and 10. Numerical results show that the convective heat transfer effects of nanofluids are higher than that of the base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The results showed that the average Nusselt number increases with the increasing of nanoparticle volume fraction and Rayleigh number, but opposite trend is observed when Hartmann number increases. Chen et al [29] used the lattice Boltzmann method to investigated the natural and mixed convection of Al2O3/water nanofluid in a square enclosure. They found that adding nanoparticles on the properties of nanofluids is enlarged in mixed convection situation.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the average Nusselt number increases with the increasing of nanoparticle volume fraction and Rayleigh number, but opposite trend is observed when Hartmann number increases. Chen et al [29] used the lattice Boltzmann method to investigated the natural and mixed convection of Al2O3/water nanofluid in a square enclosure. They found that adding nanoparticles on the properties of nanofluids is enlarged in mixed convection situation.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [12] implemented LBM to study free and mixed convection of Al 2 O 3 containing nanofluid. The designed geometry in their study was a square enclosure.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, the applications of new nanomaterials are under intense research in the materials science [1]. Another prospective subject of studies are nanoliquids containing small amounts of nanoparticles in, e.g., water solutions [2]. Consequently, great attention of researchers over last decades is paid to the production [3,4], characterization of properties [5][6][7][8], and applications of new types of nanoparticles and structures based on them [9].…”
Section: Introductionmentioning
confidence: 99%